Pengaruh Metode Cooperative Learning Tipe Tari Bambu Terhadap Kemampuan Berpikir Kritis Siswa Pada Pembelajaran IPS Sekolah Dasar - Sinta Maria Dewi; Anita Monica Risma (LPPM Universitas Buana Perjungan Karawang, 2019)
This study aims to determine the differences between cooperative learning methods of bamboo dance type on critical thinking skills of fourth grade students in social studies learning. This research is a type of quantitative research. The population used in this study were all fourth grade students, amounting to 85 students. By taking a sample of 10% of the members of the population, the sample was 40 students, 20 students in the experimental class and 20 students in the control class. The technique of collecting data through tests of critical thinking skills of class IV students in social studies learning. Data analysis techniques to test hypotheses are done by calculating the statistics of independent sample tests. The results showed that the values of the experimental class and the control class were different. With the average value of the end of the experimental class 57.75 higher than the final value of the control class of 47.60. Based on the results of the calculation of the hypothesis test shows that the probability value (significance) is 0,000. Because the significance value of 0,000 <α = 0.05, meaning that this proves that there are differences in the use of the method of cooperative learning type of bamboo dance on critical thinking skills of fourth grade students in social studies learning.